2014
DOI: 10.1016/j.ajpath.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota Protects against Ischemia/Reperfusion-Induced Intestinal Injury through Nucleotide-Binding Oligomerization Domain-Containing Protein 2 (NOD2) Signaling

Abstract: Nucleotide-binding oligomerization domain-containing protein 2 (NOD2), an intracellular pattern recognition receptor, induces autophagy on detection of muramyl dipeptide (MDP), a component of microbial cell walls. The role of bacteria and NOD2 signaling toward ischemia/reperfusion (I/R)-induced intestinal injury response is unknown. Herein, we report that I/R-induced intestinal injury in germ-free (GF) C57BL/6 wild-type (WT) mice is worse than in conventionally derived mice. More important, microbiota-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 67 publications
1
18
0
1
Order By: Relevance
“…Diagram of the mechanisms of miR-29b-3p in controlling II/R damage. MiR-29b-3p decreased the expression levels of p-TAK1 and p65 via targeting TRAF3 to alleviate apoptosis and inflammation caused by II/R II/R injury-induced SIRS and MODS can lead to death in patients (L. Liu et al, 2018;Perez-Chanona, Mühlbauer, & Jobin, 2014;Rivers et al, 2001). As demonstrated in this study, II/R injury aggravated intestinal mucosa inflammation and apoptosis which can eventually cause SIRS and MODS.…”
Section: Figuresupporting
confidence: 53%
See 1 more Smart Citation
“…Diagram of the mechanisms of miR-29b-3p in controlling II/R damage. MiR-29b-3p decreased the expression levels of p-TAK1 and p65 via targeting TRAF3 to alleviate apoptosis and inflammation caused by II/R II/R injury-induced SIRS and MODS can lead to death in patients (L. Liu et al, 2018;Perez-Chanona, Mühlbauer, & Jobin, 2014;Rivers et al, 2001). As demonstrated in this study, II/R injury aggravated intestinal mucosa inflammation and apoptosis which can eventually cause SIRS and MODS.…”
Section: Figuresupporting
confidence: 53%
“…II/R injury‐induced SIRS and MODS can lead to death in patients (L. Liu et al, ; Perez‐Chanona, Mühlbauer, & Jobin, ; Rivers et al, ). As demonstrated in this study, II/R injury aggravated intestinal mucosa inflammation and apoptosis which can eventually cause SIRS and MODS.…”
Section: Discussionmentioning
confidence: 99%
“…While the aforementioned work supports a role for the intestinal microbiota in exacerbating I/R injury, results of recent studies indicated that conventionally derived mice with an intact commensal bacterial population exhibited less injury after intestinal or renal I/R when compared to that noted in germ-free mice (379, 632, 846, 847). The protection against intestinal I/R injury was abrogated in mice that were genetically deficient in nucleotide-binding oligomerization domain-containing protein 2 (Nod2), an intracellular pattern recognition receptor (PPR) that induces autophagy on detection of the microbial cell wall component, muramyl dipeptide (632).…”
Section: Gut Microbiome and I/rmentioning
confidence: 98%
“…The protection against intestinal I/R injury was abrogated in mice that were genetically deficient in nucleotide-binding oligomerization domain-containing protein 2 (Nod2), an intracellular pattern recognition receptor (PPR) that induces autophagy on detection of the microbial cell wall component, muramyl dipeptide (632). Treatment of Nod2 −/− with the autophagy inducer rapamycin protected against I/R injury.…”
Section: Gut Microbiome and I/rmentioning
confidence: 99%
“…Inflammatory cytokines play an important role in the pathogenesis of ischemia–reperfusion induced injury . Increased production of IL‐6, TNF, IL‐1b and the neutrophil‐recruiting chemokine CXCL2 is associated with tissue damage during intestinal ischemia–reperfusion injury . Our results demonstrate that early induction of superoxide in the intestine at 1 h of ischemia precedes the induction of IL‐1b, CXCL2, and IL‐6 cytokines in ischemic intestine during reperfusion.…”
Section: Discussionmentioning
confidence: 95%